Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Motivasi Berprestasi dan Keterampilan Metakognisi pada Siswa SMP - Dian Purnama Santi (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2019)
This study aimed to describe and explain the differences of achievement motivation and metacognition skill between students by using the problem based learning model (PBL) with direct instruction model (DI). This study was a quasi experimental with non equivalent pretest posttest control group design. This study was conducted at SMP Negeri 1 Petang using population of 307 students. Samples were taken by simple random sampling technique to obtain an experimental group (VIII E) and a control group (VIII D). The experimental group was treated by PBL and the control group was treated by DI. Data was collected by achievement motivation questionnaire and metacognition skills test. Data was analyzed by descriptive and hypotheses was tested by Manova. The Hypothesis test results showed that (1) There were differences of students' achievement motivation and metacognition skills who study with PBL and DI. (2) There were significant differences of students’ achievement motivation who studied with PBL and DI. (3) There ware significant differences of students’ metacognition skills who studied with PBL and DI.